Rigidity and flexibility of surface groups - Grácio, Clara (2004)
The aim of this work is the °exibility of the hyperbolic surfaces. The results are about °exibility and geometrical boundedness. Bers are stated the universal property for all hyperbolic surface of ¯nite area where introduced the constant of boundedness. We determine this constant, using symbolic dynamics.